Safety, tolerability, and immunogenicity of two Zika virus DNA vaccine candidates in healthy adults: randomised, open-label, phase 1 clinical trials. Issue 10120 (10th February 2018) - Gaudinski, Martin R; Houser, Katherine V; Morabito, Kaitlyn M; Hu, Zonghui; Yamshchikov, Galina; Rothwell, Ro Shauna; Berkowitz, Nina; Mendoza, Floreliz; Saunders, Jamie G; Novik, Laura; Hendel, Cynthia S; Holman, LaSonji A; et al.
Summary: Background: The Zika virus epidemic and associated congenital infections have prompted rapid vaccine development. We assessed two new DNA vaccines expressing premembrane and envelope Zika virus structural proteins. Methods: We did two phase 1, randomised, open-label trials involving healthy adult volunteers. The VRC 319 trial, done in three centres, assessed plasmid VRC5288 (Zika virus and Japanese encephalitis virus chimera), and the VRC 320, done in one centre, assessed plasmid VRC5283 (wild-type Zika virus). Eligible participants were aged 18–35 years in VRC19 and 18–50 years in VRC 320. Participants were randomly assigned 1:1 by a computer-generated randomisation schedule prepared by the study statistician. All participants received intramuscular injection of 4 mg vaccine. In VRC 319 participants were assigned to receive vaccinations via needle and syringe at 0 and 8 weeks, 0 and 12 weeks, 0, 4, and 8 weeks, or 0, 4, and 20 weeks. In VRC 320 participants were assigned to receive vaccinations at 0, 4, and 8 weeks via single-dose needle and syringe injection in one deltoid or split-dose needle and syringe or needle-free injection with the Stratis device (Pharmajet, Golden, CO, USA) in each deltoid. Both trials followed up volunteers for 24 months for the primary endpoint of safety, assessed as local and systemic reactogenicity in the 7 days after each vaccination and all adverse events in the 28 days after each vaccination. The secondary endpoint in both trials was immunogenicity 4 weeks after last vaccination. These trials are registered with ClinicalTrials.gov, numbers NCT02840487 and NCT02996461 . Findings: VRC 319 enrolled 80 participants (20 in each group), and VRC 320 enrolled 45 participants (15 in each group). One participant in VRC 319 and two in VRC 320 withdrew after one dose of vaccine, but were included in the safety analyses. Both vaccines were safe and well tolerated. All local and systemic symptoms were mild to moderate. In both studies, pain and tenderness at the injection site was the most frequent local symptoms (37 [46%] of 80 participants in VRC 319 and 36 [80%] of 45 in VRC 320) and malaise and headache were the most frequent systemic symptoms (22 [27%] and 18 [22%], respectively, in VRC 319 and 17 [38%] and 15 [33%], respectively, in VRC 320). For VRC5283, 14 of 14 (100%) participants who received split-dose vaccinations by needle-free injection had detectable positive antibody responses, and the geometric mean titre of 304 was the highest across all groups in both trials. Interpretation: VRC5283 was well tolerated and has advanced to phase 2 efficacy testing. Funding: Intramural Research Program of the Vaccine Research Center, National Institute of Allergy and Infectious Diseases, National Institutes of Health.